Commentary on the Applications of Blended Learning in the Teaching and Learning Process – A Review - Kahengoda Mudiyanselage Niranga Thanuja Bandara; Balasooriya Pathiranage Ajith Jayaweera (Journal of Research in Education and Pedagogy, 2024)
Blended learning, an innovative approach that combines traditional face-to-face (FTF) instruction with online elements, has gained prominence in education. This article provides a comprehensive overview of blended learning, including its definition, advantages, disadvantages, and various factors that affect the effectiveness of this teaching and learning approach. It also explores students’ and teachers’ perceptions of blended learning and the challenges and issues that may arise in its implementation. Blended learning has been found to provide several benefits such as personalized learning, flexibility, improved engagement, cost-effectiveness, accessibility, and real-world skill development. However, it also presents challenges related to technological dependence, digital inequality, reduced face-to-face interaction, and assessment difficulties. Instructors may face challenges in terms of preparation, time management, and scheduling. Factors affecting learning in a blended environment include pedagogical approaches, technology infrastructure, teacher skills and training, student engagement, assessment methods, cultural and social context, and time management. Students and teachers generally perceive blended learning positively, citing improvements in learning outcomes and teaching practices. While blended learning offers a sound pedagogical approach, successful implementation requires addressing technical barriers, ensuring engagement, effective assessment and evaluation methods, effective time management, and providing instructor training and support. Data privacy and security, social isolation, and course redesign are also important considerations in implementing blended learning. In conclusion, blended learning is a versatile and effective educational approach with many advantages and challenges. To ensure its success, careful planning, continuous evaluation, and support for educators and learners are essential to create rich learning environments in a rapidly evolving educational environment.